Mathematical Model for the Optimization of Municipal Solid Waste Management - Barma, Modu; Biniyamin, Hamisu Kyauta; Modibbo, Umar Muhammad; Gaya, Hammandikko Mu'azu (Frontiers in Sustainability, 2022)
Solid waste management (SWM) is central to any nation experiencing rapid expansion via urbanization, migration, and population growth. Waste management is crucial in every country since it can directly affect people's health and the environment. For example, cholera outbreaks in some developing countries like Nigeria are common in congested areas, especially during the particular season. Therefore, efficient and effective Municipal Solid Waste Management (MSWM) is necessary. This study developed a mixed-integer optimization model for MSW of Kano State Nigeria. The model optimizes the total cost of SWM, which includes the cost of transporting different types of waste between other locations plus the fixed cost of establishing and maintaining/operating some facilities. The analysis further reveals that the government should establish 20 standard collection centers having a capacity of 60 tons. With one combusting and hazardous centers each having capacity of 391 and 81 tons, respectively, and two recycling, composting, and disposal centers, each having a total of 240, 200, and 113 tons, respectively. Incorporating the recovery process in the SWM policy reduces the number of disposal centers, and more than 80% of the daily generated wastes are recoverable. Hence, the government would save considerable resources (costs) and generate revenues from the approach once implemented.